Biomedical gradient high-entropy composite strengthened coating with interstitial strengthening phase and preparation method of biomedical gradient high-entropy composite strengthened coating
By using double-ray plasma surface metallurgy, laser cladding and magnetron sputtering technology to form a high-entropy alloy deposition layer on the surface of biomedical titanium materials, the loosening problem caused by insufficient biological binding and thermal expansion in the human body is solved, and the problem of loosening caused by the difference in thermal expansion of titanium materials is significantly improved. The material's wear resistance and biocompatibility are achieved.
Patent Information
- Application Number
- CN202411116042.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-14
- Publication Date
- 2024-12-17
AI Technical Summary
The existing biomedical titanium and titanium alloy materials are easily covered by fibers after implantation in the human body. The biological bonding is insufficient, and the thermal expansion coefficient is different leads to loosening. It is easy to corrode and wear in a body fluid environment with abundant oxygen ions. It is difficult to use surface modification technology. Improve performance.
Using Shuanghui plasma surface metallurgy, laser cladding and magnetron sputtering technology to form a high-entropy alloy deposition layer on the surface of metal substrates, including Fe, Co, Ti, Ni, Al, Cr, Cu, Nb, Ta, Hf, Zr , W and other alloy elements and C, B, N, and O gap strengthening elements to form a gradient high entropy composite reinforcement coating with gap strengthening phases.
It significantly improves the wear resistance, corrosion resistance and biocompatibility of the material, enhances the binding force with bone tissue, overcomes the problem of insufficient bonding strength between traditional coatings and substrates, increases the microhardness by 7.5 times, and reduces the wear rate. 16.4%, meeting clinical biocompatibility requirements.
Smart Images

Figure CN119144952A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alloy surface modification, and is a biomedical gradient high entropy composite strengthening coating with an interstitial strengthening phase and a preparation method thereof. Background Art
[0002] At present, in clinical medical applications, common biomedical metal materials are mainly titanium and titanium alloys, magnesium alloys, cobalt-chromium alloys and medical stainless steel, etc. Among them, titanium and titanium alloys are widely used in the manufacture of human implant materials such as artificial bones and artificial joints due to their good biocompatibility, mechanical strength, wear resistance and corrosion resistance. However, after being implanted into the human body, the surface of titanium and titanium alloys is usually easily covered by human fibrous connective tissue, which is not easy to produce a good biological combination with human bone tissue. In addition, the thermal expansion coefficients of natural bones and titanium and titanium alloys are very different, so they are easy to loosen in the human body, which in turn affects the effectiveness of long-term implantation of titanium and titanium alloys in the human body. At the same time, since the human body fluid contains a large amount of oxygen and is rich in various ions, the service environment of human implant materials after implantation is relatively harsh. Under the combined action of the friction process of the patient's daily activities, the human implant is easily corroded and worn.
[0003] Surface modification technology is a type of heat treatment technology that uses chemical or physical methods to change the chemical composition or organizational structure of the surface of a material or workpiece to improve the performance of machine parts or materials. Therefore, the surface of titanium and titanium alloys can be modified to further improve the wear resistance and corrosion resistance of titanium and titanium alloys in the human body environment to meet the needs of clinical applications.
[0004] In recent years, the surface modification technology for medical titanium and titanium alloys has developed rapidly, including ion implantation, anodization, vapor deposition and micro-arc oxidation. However, the surface modified alloy layer prepared on the surface of medical titanium and titanium alloys by various surface modification technologies is mainly based on traditional alloys, which is not enough to improve the performance. At the same time, the coatings prepared by these commonly used surface modification technologies have insufficient bonding strength with the substrate, and a single modification method is difficult to meet the requirements of multiple biological performance. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a biomedical gradient high entropy composite reinforcement coating with an interstitial reinforcement phase and a preparation method thereof.
[0006] The technical solution for achieving the purpose of the present invention is:
[0007] A biomedical gradient high entropy composite strengthening coating with an interstitial strengthening phase is a high entropy alloy deposition layer formed on the surface of a metal substrate by double glow plasma surface metallurgy, laser cladding and magnetron sputtering technology; wherein:
[0008] The metal substrate is pure titanium or titanium alloy;
[0009] The high entropy alloy deposition layer contains at least five of the alloying elements Fe, Co, Ti, Ni, Al, Cr, Cu, Nb, Ta, Hf, Zr, W and Mo, and at least two of the interstitial strengthening elements C, B, N and O.
[0010] The high entropy alloy deposition layer is formed on the surface of the metal substrate, and includes a permeation layer formed by magnetron sputtering technology, a permeation layer formed by laser cladding technology, a permeation layer formed by double glow plasma solid surface metallurgy, and a solid solution diffusion layer from the surface to the inside.
[0011] A method for preparing a biomedical gradient high entropy composite strengthening coating with an interstitial strengthening phase comprises the following steps:
[0012] 1) Preparation of the infiltration layer formed by double glow plasma solid surface metallurgy:
[0013] 1-1) Grinding, polishing, cleaning and drying the surface of the metal substrate for later use;
[0014] 1-2) inserting a rod-shaped high entropy alloy source target containing at least five elements of Fe, Co, Ti, Ni, Al, Cr, Cu, Nb, Ta, Hf, Zr, W and Mo into evenly distributed small holes on the auxiliary source barrel, and then placing the auxiliary source barrel in a double-glow plasma solid surface metallurgy device, suspending a metal substrate in the auxiliary source barrel through a conductive member, and making the metal substrate not contact the high entropy alloy source target;
[0015] 1-3) depositing a rod-shaped high entropy alloy source target and at least two of the interstitial strengthening elements C, B, N, and O on the surface of the metal substrate treated in step 1-1) by a double glow plasma solid surface metallurgy device to obtain a double glow plasma surface metallurgy permeation layer having an interstitial strengthening phase;
[0016] 2) Preparation of laser cladding technology infiltration layer:
[0017] 2-1) cleaning and drying the metal substrate having the double glow plasma surface metallurgical infiltration layer obtained in step 1) for later use;
[0018] 2-2) preparing high entropy alloy ingots by arc melting at least five metal elements selected from Fe, Co, Ti, Ni, Al, Cr, Cu, Nb, Ta, Hf, Zr, W and Mo, respectively, crushing the obtained high entropy alloy ingots into alloy powders, weighing the alloy powders in proportion, and then ball milling and mixing them, and then diluting the mixed alloy powders with anhydrous ethanol until they are viscous and uniformly adhere to the surface of the metal substrate obtained in step 2-1) and drying them;
[0019] 2-3) The metal substrate dried in step 2-2) is subjected to laser cladding surface treatment using a CO2 laser under argon protection, thereby forming a laser cladding technology diffusion layer on the surface of the double glow plasma surface metallurgical diffusion layer;
[0020] 3) Preparation of magnetron sputtering technology permeation coating:
[0021] 3-1) cleaning and drying the metal substrate with the double glow plasma surface metallurgical infiltration layer and the laser cladding technology infiltration layer obtained in step 2) for later use;
[0022] 3-2) mixing at least five metal powders of Fe, Co, Ti, Ni, Al, Cr, Cu, Nb, Ta, Hf, Zr, W and Mo in proportion by ball milling to alloy them, and then sintering them under pressure to prepare a high entropy alloy target;
[0023] 3-3) In a magnetron sputtering device, the metal substrate obtained in step 3-1) is placed at the anode, the high entropy alloy target obtained in step 3-2) is placed at the cathode, the vacuum chamber of the magnetron sputtering device is closed, argon gas is filled into the vacuum chamber after evacuation, and then the magnetron sputtering device is ion cleaned; after the ion cleaning is completed, magnetron sputtering is performed in an argon atmosphere to form a magnetron sputtering technology diffusion layer on the surface of the laser cladding technology diffusion layer;
[0024] 4) Post-treatment: The metal substrate obtained after step 3) is sealed, and heat-treated at 700-800° C. for 1-8 hours in a heat treatment furnace, and then quenched to obtain a biomedical gradient high entropy composite reinforcement coating with an interstitial reinforcement phase on the metal substrate.
[0025] In step 1-2), the high entropy alloy source target is prepared by selecting at least five metal elements of Fe, Co, Ti, Ni, Al, Cr, Cu, Nb, Ta, Hf, Zr, W and Mo in proportion, cleaning and drying them respectively, and then vacuum arc melting them. After repeated melting for five times or more, the alloy block obtained by melting is placed in a mold and shaped into a rod-shaped high entropy alloy source target of uniform size.
[0026] In step 1-3), the gap strengthening element is introduced into the double glow plasma solid surface metallurgy equipment in the form of methane and nitrogen. The treatment process of the double glow plasma solid surface metallurgy equipment is:
[0027] 1-3-1) The double glow plasma solid surface metallurgical equipment is bombarded before infiltration, and the processing steps are as follows:
[0028] a) Clean the dust and metal debris in the furnace of the double-glow plasma solid surface metallurgical equipment and close the furnace door of the equipment;
[0029] b) The vacuum degree in the furnace of the double glow plasma solid surface metallurgy equipment is drawn to the set range;
[0030] c) turning on the source pulse power supply of the double glow plasma solid surface metallurgy equipment, gradually increasing the voltage and current of the power supply, so that the auxiliary source barrel and the metal substrate produce glow discharge and arcing, bombarding and cleaning the high entropy alloy source target and the metal substrate, and the bombardment and cleaning are completed after the arcing phenomenon disappears;
[0031] 1-3-2) Introduce argon, ammonia and methane with a purity of ≥99.99% into the equipment, wherein the flow rate of argon is 5-40mL / min, and the flow rates of ammonia and methane are 1-5mL / min. The vacuum degree is adjusted to a working pressure of 20-60Pa by adjusting the flow rates of the three gases;
[0032] 1-3-3) gradually increase the voltage and current of the source pulse power supply of the equipment to make the temperature of the metal substrate 800-1400°C, and keep it warm for 2-5 hours. After the warming time is over, turn off the flow of argon, ammonia and methane to complete the infiltration deposition;
[0033] 1-3-4) Carry out ion nitriding treatment:
[0034] Ⅰ) introducing ammonia gas with a purity of ≥99.99% into the double glow plasma solid surface metallurgy equipment at a flow rate of 80-240 mL / min, controlling the glow thickness to be about 4-8 mm, the nitriding temperature to be 500-550° C., and adjusting the flow rate of ammonia gas introduced according to the glow thickness;
[0035] II) The nitriding temperature is 480-560°C, the nitriding time is 5-10 hours, the source pulse power supply voltage and current are adjusted according to the nitriding temperature, and the pulse power supply voltage is controlled at -300V to -900V;
[0036] Ⅲ) After the holding time is over, turn off the ammonia flow, turn off the power, keep pumping and allow the treated material to cool to room temperature with the furnace.
[0037] In step 2-2), the ball milling process is as follows: under vacuum conditions, the ball milling speed is 30-90 r / min, the ball-to-material ratio is 15:1-18:1, the ball milling time is not less than 4 hours, and the alloy powder is obtained after sufficient mixing, and the particle size of the powder is 200-300 mesh.
[0038] In step 2-3), the purity of the argon gas is ≥99.99%, and the gas flow rate is 20-30 L / min; the laser cladding surface treatment process is: the laser power is 3000-4000 W, the scanning speed is 3-6 mm / s, and the spot diameter D is 2-4 mm.
[0039] In step 3-2), the ball milling process is as follows: under vacuum conditions, the ball milling speed is 240 to 280 r / min, the ball-to-material ratio is 10:1 to 12:1, the ball milling time is 1.5 to 2 hours, the inversion frequency is 30 to 45 Hz, and the alloy powder is obtained after sufficient mixing, and the particle size of the powder is 50 to 100 μm.
[0040] In step 3-2), the pressure sintering process is as follows: under argon protection, the pressure in the pressure sintering furnace is 200-300 MPa, the sintering temperature range is 900-1000° C., and the holding time is 5-10 minutes.
[0041] In step 3-3), the ion cleaning is to clean the dust and metal debris in the magnetron sputtering equipment, and then evacuate to 3×10-2Pa~3×10-3Pa, introduce argon gas, and adjust the gas flow rate to stabilize the gas pressure at 3~5Pa; finally, turn on the negative bias power supply, adjust the negative bias to the range of 500~800V, and perform ion bombardment glow cleaning for 15~20 minutes.
[0042] In step 3-3), the process parameters of the magnetron sputtering are: anode substrate material temperature of 180-200°C, sputtering time of 40-50min, target substrate distance of 5-10cm, target power of 90-110W, and argon gas flow rate of 55-65sccm.
[0043] The present invention provides a biomedical gradient high-entropy composite strengthening coating with an interstitial strengthening phase and a preparation method thereof, which integrates the composite technology of "double glow plasma surface metallurgy + laser cladding + magnetron sputtering" with the surface modification of biomedical implant materials, interstitial solid solution strengthening of high-entropy alloys, and biomedical high-entropy alloy films (coatings), adopts medical implant materials as substrates, utilizes interstitial solid solution strengthening of high-entropy alloys to effectively improve the performance of high-entropy alloys, and is easy to prepare. The advantages of double glow plasma surface metallurgy technology, such as high bonding strength, low cost, metallurgical bonding with the substrate, and good organizational structure characteristics, and the advantages of laser cladding technology, such as controllable coating thickness, good quality and stability, are combined with the huge application potential of biomedical high-entropy alloy films (coatings), thereby greatly improving the wear resistance, corrosion resistance, stability and biocompatibility of medical implant materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 A schematic cross-sectional view of a biomedical gradient high entropy alloy composite strengthening layer having an interstitial strengthening phase according to an embodiment of the present invention;
[0045] Figure 2 is a schematic diagram of the auxiliary source bucket structure used in an embodiment of the present invention;
[0046] Figure 3A schematic diagram of inserting a source target material prepared in an embodiment of the present invention into an auxiliary source barrel;
[0047] Figure 4 It is a schematic diagram of a double glow plasma surface metallurgy equipment in an embodiment of the present invention;
[0048] Figure 5 Schematic diagram of the device used when performing laser cladding technology in an embodiment of the present invention. DETAILED DESCRIPTION
[0049] The present invention is further explained below with reference to the accompanying drawings and embodiments, but the present invention is not limited thereto.
[0050] Example:
[0051] like Figure 1 As shown, a biomedical gradient high entropy alloy composite strengthening layer with an interstitial strengthening phase provided by an embodiment of the present invention comprises a metal substrate and a high entropy alloy deposition layer with an interstitial strengthening phase deposited on the surface of the metal substrate by a composite technology of "double glow plasma surface metallurgy + laser cladding + magnetron sputtering", wherein the high entropy alloy deposition layer comprises at least five alloying elements (Fe, Co, Ti, Ni, Al, Cr, Cu, Nb, Ta, Hf, Zr, W and Mo) and two interstitial strengthening elements (C, B, N, O). The high entropy alloy deposition layer with an interstitial strengthening phase deposited on the surface of the metal substrate by a composite technology of "double glow plasma surface metallurgy + laser cladding + magnetron sputtering" is a new type of biomedical gradient high entropy alloy composite strengthening layer with an interstitial strengthening phase that is metallurgically bonded. This new type of biomedical gradient high-entropy alloy composite reinforcement layer with an interstitial reinforcement phase can maintain the good mechanical properties of the matrix material while having good wear resistance, corrosion resistance and biological stability in the human body fluid environment, overcoming the problems of insufficient bonding strength between the coating and the matrix in existing surface modification technologies.
[0052] Specifically, the metal matrix material to be infiltrated in this example is a pure titanium sample with a size of 180mm×15mm×4mm; the high-entropy alloy deposition layer is composed of six alloy elements of Fe, Co, Cr, Al, Ti, and Cu and two interstitial strengthening elements of C and N.
[0053] The method for preparing the above-mentioned biomedical gradient high entropy alloy composite strengthening layer with interstitial strengthening phase provided in this example includes three parts: preparing a double glow plasma solid surface metallurgical infiltration coating, preparing a laser cladding technology infiltration coating, and preparing a magnetron sputtering technology infiltration coating;
[0054] In the first aspect, a double glow plasma solid surface metallurgical infiltration coating is prepared, comprising the following steps:
[0055] Prepare a metal matrix material, grind and polish it, then perform ultrasonic cleaning, and finally dry the matrix for use; prepare a rod-shaped FeCoCrAl0.5TiCu0.5 high-entropy alloy source target; insert the prepared rod-shaped high-entropy alloy source target into the evenly distributed small holes on the homemade auxiliary source barrel, the size of the auxiliary source barrel is φ100×150mm; place the auxiliary source barrel with the target inserted in a double-glow plasma solid surface metallurgy equipment, the schematic diagram of the auxiliary source barrel is as shown in Figure 2 As shown, the schematic diagram after the target material is inserted into the auxiliary source barrel is as follows Figure 3 As shown; the metal substrate is suspended in the auxiliary source barrel through a conductive member, and the metal substrate is not in contact with the high entropy alloy source target, as shown Figure 4 As shown; argon, methane and nitrogen are introduced into a double glow plasma solid surface metallurgy device, and the rod-shaped high entropy alloy source target material and the interstitial strengthening elements are deposited on the surface of the metal matrix material through the relevant operation steps of solid surface metallurgy to form a double glow plasma surface metallurgy gradient high entropy alloy deposition layer with an interstitial strengthening phase.
[0056] Specifically, the specific steps for preparing the rod-shaped FeCoCrAl0.5TiCu0.5 high entropy alloy source target are:
[0057] At least five pure metal elements of Fe, Co, Ti, Ni, Al, Cr, Cu, Nb, Ta, Hf, Zr, W and Mo with a purity of not less than 99.95% are selected. In this example, six pure elements of Fe, Co, Cr, Al, Ti and Cu are selected as raw materials. According to the composition of Fe, Co, Cr, Al0.5, Ti and Cu0.5, 40 portions of materials are weighed and proportioned, each portion is 20 grams, that is, 40 FeCoCrAl0.5TiCu0.5 high entropy alloy source targets. After the materials are prepared, ultrasonic cleaning and drying are carried out for use. The vacuum arc melting technology is used for preliminary melting. First, the vacuum arc melting furnace is inspected and cleaned. The debris in the furnace is cleaned with alcohol. After cleaning, the raw materials are put in, the furnace cover is closed, and the power supply and cooling circulation system are turned on. Turn on the vacuum system, evacuate the vacuum to below 20Pa, introduce argon gas for gas washing, and repeat the vacuum washing at least 3 times. Then the vacuum degree is evacuated to 3.0×10-3Pa, and argon is filled to 0.08Pa to form an inert atmosphere in the furnace chamber. The magnetic stirring function needs to be turned on during the smelting process. Each sample needs to be repeatedly turned over and melted more than 3 times to ensure uniform smelting. Finally, the sample ingot is turned into the suction casting mold groove. The mold cavity size is 8mm in diameter and 10mm in length. First, the edge is heated once, and then heated to the center to melt. When it melts to the surface, the current is increased to instantly open the suction casting valve, and the arc melting power supply is turned off. After the sample, cavity, and electrode are cooled, the gas is released, the mold is removed, and the smelted rod-shaped source target is taken out to obtain the high entropy alloy source target. After the smelting is completed, after cooling for 1h, the vent valve is opened. The furnace cover can be opened to obtain the sample after the furnace becomes normal pressure. After cooling to room temperature, the equipment is cleaned with alcohol, the furnace cover is closed, the lock is locked, and the vacuum turntable is evacuated. The water and power are cut off, and the smelting is completed.
[0058] Specifically, the interstitial strengthening elements are introduced into the equipment in the form of methane and ammonia to carry out double glow plasma solid surface metallurgy.
[0059] Specifically, the double glow plasma solid surface metallurgy step includes the following steps:
[0060] The method comprises the following steps: performing bombardment cleaning before permeation plating; introducing argon, ammonia and methane with a purity of ≥99.99% into the double glow plasma solid surface metallurgy equipment, wherein the argon flow rate is 5-40 mL / min, and the ammonia and methane flow rates are 1-5 mL / min, and adjusting the flow rates of the three gases so that the vacuum degree reaches a working gas pressure of 20-60 Pa; gradually increasing the voltage and current of the source pulse power supply, at which time the metal substrate begins to heat up sharply, and at the same time using an infrared thermometer device to test the substrate temperature, so that the metal substrate temperature is 800-1400°C, and the insulation time is 2-5 hours. After the insulation time is over, the argon, ammonia and methane flow rates are closed to complete the permeation plating deposition, and after the permeation plating deposition is completed, an ion nitriding operation is performed.
[0061] Specifically, the bombardment cleaning process before the infiltration plating includes the following steps:
[0062] Clean the dust and metal debris in the furnace body of the plasma solid surface metallurgical equipment, close the furnace door of the plasma solid surface metallurgical equipment, start the mechanical pump to evacuate, and evacuate the vacuum degree in the furnace body of the plasma solid surface metallurgical equipment to below 1800Pa, turn on the source pulse power supply, and gradually increase the voltage and current of the power supply. At this time, the auxiliary source barrel and the metal substrate produce glow discharge and arcing, and the high entropy alloy source target and the metal substrate are bombarded and cleaned. After the arcing phenomenon disappears, the bombardment and cleaning are completed, and then the infiltration deposition step is performed.
[0063] Specifically, after the permeation deposition step, the ion nitridation treatment includes the following steps:
[0064] Ammonia with a purity of ≥99.99% is introduced into the double glow plasma solid surface metallurgy equipment at a flow rate of 80 to 240 mL / min, and the glow thickness is controlled to be about 4 to 8 mm. The flow rate of ammonia introduced is adjusted according to the observed glow thickness. The greater the ammonia flow rate, the higher the gas pressure and the thinner the glow thickness. The nitriding temperature is 480 to 560°C, and the nitriding time is 5 to 10 hours. The source pulse power supply voltage and current are adjusted according to the nitriding temperature, and the pulse power supply voltage is controlled at -300V to -900V. After the insulation time is over, the ammonia flow rate is turned off, the power supply is turned off, the mechanical pump is kept pumping, and the high entropy alloy is cooled to room temperature with the furnace.
[0065] In the second aspect, the laser cladding technology is used to prepare the infiltration coating, including the following steps:
[0066] The material after the double glow plasma solid surface metallurgy treatment is ultrasonically cleaned in anhydrous ethanol for 20 minutes to remove impurities remaining on the surface, and then dried with a hair dryer and placed in a 50°C drying oven for 2 hours for use; at least five pure metal elements of Fe, Co, Ti, Ni, Al, Cr, Cu, Nb, Ta, Hf, Zr, W and Mo with a purity of not less than 99.95%, and this example uses six pure elements of Fe, Co, Cr, Al, Ti and Cu as raw materials, ultrasonically clean and dry various raw materials, and then prepare high entropy alloy ingots by arc melting, and vibrate and crush them into alloy powders with smaller particle sizes, and prepare them according to the ratio of Fe, Co, Cr, Al0.5, Ti, C u0.5 component ratio is weighed in turn for ball milling and mixing. In this example, the parameters of ball milling are rotation speed 40r / min, ball-to-material ratio 16:1, and ball milling time 5h; the average particle size after ball milling is 250 mesh, and the ball-milled powder is evenly mixed with 95% alloy powder by mass fraction and 5% anhydrous ethanol, diluted to viscosity and evenly adhered to the surface of the material after the double glow plasma solid surface metallurgy treatment, and then placed in a 60°C drying oven for drying for 5h, and then under the protection of argon at a gas flow rate of 25L / min, a CO2 laser is used. In this example, the laser power is set to 3500W, the scanning speed is set to 5mm / s, and the spot diameter D is set to 3mm to perform laser cladding surface treatment on the prefabricated coating.
[0067] In a third aspect, a magnetron sputtering coating is prepared, comprising the following steps:
[0068] The material after the double glow plasma solid surface metallurgy and laser cladding treatment is ultrasonically cleaned in anhydrous ethanol for 20 minutes to remove impurities remaining on the surface, dried with a hair dryer and placed in a 50°C drying oven for 2 hours for use; at least five pure metal elements of Fe, Co, Ti, Ni, Al, Cr, Cu, Nb, Ta, Hf, Zr, W and Mo with a purity of not less than 99.95%, this example uses six pure elements of Fe, Co, Cr, Al, Ti and Cu as raw materials, ultrasonically clean and dry each type of raw material, and then prepare a high entropy alloy ingot by arc melting, vibrate and crush it into alloy powder with a smaller particle size, weigh the metal powders in turn according to the composition ratio of Fe, Co, Cr, Al0.5, Ti, and Cu0.5, and ball mill to mix the powder. The ball milling parameters in this example are a ball milling speed of 260r / min, a ball-to-material ratio of 11:1, and a ball milling time of 1:1. The time is 1.5 hours, the inversion frequency is 40Hz, and the alloy powder is obtained after being fully mixed. The average particle size of the powder is about 80μm. Then, under the protection of argon gas, pressure sintering is performed to form a high entropy alloy target. In this example, the pressure sintering parameters are pressure 240MPa, sintering temperature 1000℃, and holding time is 10 minutes; then the high entropy alloy target is placed on the cathode in the magnetron sputtering equipment, and the material treated in claim 9 is placed on the anode. The vacuum chamber is closed, evacuated and argon gas is passed for ion bombardment glow cleaning. In this example, the ion cleaning parameters are vacuum degree 3×10-3Pa, stable gas pressure 5Pa, negative bias 700V, and cleaning time 15 minutes; then, under the protection of argon gas with a gas flow rate of 60sccm, magnetron sputtering is performed to deposit a high entropy alloy coating. In this example, the temperature of the anode substrate material is 200℃, the sputtering time is 50min, the target substrate distance is 8cm, and the target power is 100W. The schematic diagram of the magnetron sputtering equipment used in this embodiment is as follows Figure 5 shown.
[0069] Specifically, after the biomedical gradient high entropy alloy composite strengthening layer with an interstitial strengthening phase is prepared, a post-heat treatment is performed, comprising the following steps:
[0070] The treated material is sealed and then heat treated in a heat treatment furnace at a temperature of 700 to 1000° C. for 1 to 8 hours. After the heat treatment, the treated material is quenched in an ice-water mixture and then dried.
[0071] In this example, the composite technology of "double glow plasma surface metallurgy + laser cladding + magnetron sputtering" is integrated with the surface modification of biomedical implant materials and biomedical high entropy alloy films (coatings). Medical implant materials are used as the substrate. The advantages of double glow plasma surface metallurgy technology such as high bonding strength, low cost, metallurgical bonding with the substrate, and good organizational structure characteristics, and the advantages of laser cladding technology such as controllable coating thickness, good quality and stability are utilized. Combined with the huge application potential of biomedical high entropy alloy films (coatings), the wear resistance, corrosion resistance, stability and biocompatibility of medical implant materials are greatly improved.
[0072] The composite-strengthened high-entropy alloy with interstitial strengthening phase obtained by the above preparation method was tested, and the results are as follows:
[0073] In this example, the percentage content of each element in the biomedical gradient high entropy alloy composite strengthening layer with interstitial strengthening phase prepared on the pure titanium substrate is: iron (Fe): 19%, cobalt (Co): 17%, chromium (Cr): 18%, aluminum (Al): 10%, titanium (Ti): 19%, copper (Cu): 11%, nitrogen (N) 4.5%, carbon (C) 0.5%, constituting a surface high entropy alloy with interstitial strengthening phase. A diffusion layer and a high entropy alloy deposition layer with interstitial strengthening phase are formed on the surface of the pure titanium substrate, the diffusion layer thickness is 30μm, the double glow plasma surface metallurgy high entropy three alloy deposition layer thickness is 10μm, the laser cladding high entropy alloy deposition layer thickness is 15μm, and the magnetron sputtering high entropy alloy deposition layer thickness is 5μm. The element composition in the alloy strengthening layer diffusion layer changes slowly with depth, and is metallurgically bonded to the pure titanium substrate.
[0074] Hardness and friction and wear experiments in simulated human body fluids showed that the surface microhardness of the pure titanium substrate was 15HV, and the surface microhardness of the biomedical gradient high entropy alloy composite reinforcement layer with interstitial reinforcement phase was 1090HV, and the hardness was increased by 7.5 times; the specific wear rate of the pure titanium substrate was 19.5 (×10-3mm3N-1m-1), and the specific wear rate of the biomedical gradient high entropy alloy composite reinforcement layer with interstitial reinforcement phase was 3.2 (×10-3mm3N-1m-1), which was only 16.4% of the substrate.
[0075] Biocompatibility experiments show that in the in vitro coagulation experiment, the prothrombin time (APTT) and prothrombin time (PT) of pure titanium and the composite strengthening layer of the biomedical gradient high entropy alloy with interstitial strengthening phase are 27.5s, 11.4s and 27.9s, 12.1s respectively. In the hemolysis rate experiment, the hemolysis rate (HR) of the composite strengthening layer of pure titanium and the medical high entropy alloy with interstitial strengthening phase is 0.11% and 0.31% respectively. Both are less than 5%, which meets the requirements of medical clinical practice. In the cytotoxicity experiment, mouse cells were used for testing, and the relative value-added rates on the composite strengthening layer of pure titanium and the biomedical gradient high entropy alloy with interstitial strengthening phase were 100% and 110% respectively. The cytotoxicity rating is 0.
[0076] The above test results show that: using the above-mentioned "double glow plasma surface metallurgy + laser cladding + magnetron sputtering" composite technology, a biomedical gradient high entropy alloy composite strengthening layer with interstitial strengthening phase that meets clinical standards has been successfully prepared on the surface of pure titanium, which greatly improves its hardness and wear resistance in human simulated body fluids by about 7.5 times. The prothrombin time (APTT) and prothrombin time (PT) of pure titanium and the medical high entropy alloy composite strengthening layer with interstitial strengthening phase are similar, indicating that they have similar anti-coagulation properties; the hemolysis rate and cell proliferation rate of the medical high entropy alloy composite strengthening layer with interstitial strengthening phase are relatively higher than those of pure titanium, indicating that its hemolysis performance is relatively poor, its cytotoxicity is relatively low, and it has better cell compatibility. According to the test results, the pure titanium matrix and the biomedical gradient high entropy alloy composite reinforcement layer with interstitial reinforcement phase are compared, and the following conclusions can be drawn: the biomedical gradient high entropy alloy composite reinforcement layer with interstitial reinforcement phase significantly improves the wear resistance, hardness, human stability and biocompatibility of pure titanium, a clinical medical human implant material, and has good application prospects.
Claims
1. A biomedical gradient high entropy composite strengthening coating with an interstitial strengthening phase, characterized in that: It is a high entropy alloy deposition layer formed on the surface of a metal substrate by double glow plasma surface metallurgy, laser cladding and magnetron sputtering technology; among which: The metal substrate is pure titanium or titanium alloy; The high entropy alloy deposition layer contains at least five of the alloying elements Fe, Co, Ti, Ni, Al, Cr, Cu, Nb, Ta, Hf, Zr, W and Mo, and at least two of the interstitial strengthening elements C, B, N and O.
2. A biomedical gradient high entropy composite strengthening coating with an interstitial strengthening phase according to claim 1, characterized in that: The high entropy alloy deposition layer is formed on the surface of the metal substrate, and includes a permeation layer formed by magnetron sputtering technology, a permeation layer formed by laser cladding technology, a permeation layer formed by double glow plasma solid surface metallurgy, and a solid solution diffusion layer from the surface to the inside.
3. A method for preparing a biomedical gradient high entropy composite strengthening coating with an interstitial strengthening phase, characterized in that: The steps include: 1) Preparation of the infiltration layer formed by double glow plasma solid surface metallurgy: 1-1) Grinding, polishing, cleaning and drying the surface of the metal substrate for later use; 1-2) inserting a rod-shaped high entropy alloy source target containing at least five elements of Fe, Co, Ti, Ni, Al, Cr, Cu, Nb, Ta, Hf, Zr, W and Mo into evenly distributed small holes on the auxiliary source barrel, and then placing the auxiliary source barrel in a double-glow plasma solid surface metallurgy device, suspending a metal substrate in the auxiliary source barrel through a conductive member, and making the metal substrate not contact the high entropy alloy source target; 1-3) depositing a rod-shaped high entropy alloy source target and at least two of the interstitial strengthening elements C, B, N, and O on the surface of the metal substrate treated in step 1-1) by a double glow plasma solid surface metallurgy device to obtain a double glow plasma surface metallurgy permeation layer having an interstitial strengthening phase; 2) Preparation of laser cladding technology infiltration layer: 2-1) cleaning and drying the metal substrate having the double glow plasma surface metallurgical infiltration layer obtained in step 1) for later use; 2-2) preparing high entropy alloy ingots by arc melting at least five metal elements selected from Fe, Co, Ti, Ni, Al, Cr, Cu, Nb, Ta, Hf, Zr, W and Mo, respectively, crushing the obtained high entropy alloy ingots into alloy powders, weighing the alloy powders in proportion, and then ball milling and mixing them, and then diluting the mixed alloy powders with anhydrous ethanol until they are viscous and uniformly adhere to the surface of the metal substrate obtained in step 2-1) and drying them; 2-3) The metal substrate dried in step 2-2) is subjected to laser cladding surface treatment using a CO2 laser under argon protection, thereby forming a laser cladding technology diffusion layer on the surface of the double glow plasma surface metallurgical diffusion layer; 3) Preparation of magnetron sputtering technology permeation coating: 3-1) cleaning and drying the metal substrate with the double glow plasma surface metallurgical infiltration layer and the laser cladding technology infiltration layer obtained in step 2) for later use; 3-2) mixing at least five metal powders of Fe, Co, Ti, Ni, Al, Cr, Cu, Nb, Ta, Hf, Zr, W and Mo in proportion by ball milling to alloy them, and then sintering them under pressure to prepare a high entropy alloy target; 3-3) In a magnetron sputtering device, the metal substrate obtained in step 3-1) is placed at the anode, the high entropy alloy target obtained in step 3-2) is placed at the cathode, the vacuum chamber of the magnetron sputtering device is closed, argon gas is filled into the vacuum chamber after evacuation, and then the magnetron sputtering device is ion cleaned; after the ion cleaning is completed, magnetron sputtering is performed in an argon atmosphere to form a magnetron sputtering technology diffusion layer on the surface of the laser cladding technology diffusion layer; 4) Post-treatment: The metal substrate obtained after step 3) is sealed, and heat treated at 700-800° C. for 1-8 hours in a heat treatment furnace, and then quenched to obtain a biomedical gradient high entropy composite reinforcement coating with an interstitial reinforcement phase on the metal substrate.
4. The method for preparing a biomedical gradient high entropy composite strengthening coating with an interstitial strengthening phase according to claim 3, characterized in that: In step 1-2), the high entropy alloy source target is prepared by selecting at least five metal elements of Fe, Co, Ti, Ni, Al, Cr, Cu, Nb, Ta, Hf, Zr, W and Mo in proportion, cleaning and drying them respectively, and then vacuum arc melting them. After repeated melting for five times or more, the alloy block obtained by melting is placed in a mold and shaped into a rod-shaped high entropy alloy source target of uniform size.
5. The method for preparing a biomedical gradient high entropy composite strengthening coating with an interstitial strengthening phase according to claim 3, characterized in that: In step 1-3), the gap strengthening element is introduced into the double glow plasma solid surface metallurgy equipment in the form of methane and nitrogen. The treatment process of the double glow plasma solid surface metallurgy equipment is: 1-3-1) The double glow plasma solid surface metallurgical equipment is bombarded before infiltration, and the processing steps are as follows: a) Clean the dust and metal debris in the furnace of the double-glow plasma solid surface metallurgical equipment and close the furnace door of the equipment; b) The vacuum degree in the furnace of the double glow plasma solid surface metallurgy equipment is drawn to the set range; c) turning on the source pulse power supply of the double glow plasma solid surface metallurgy equipment, gradually increasing the voltage and current of the power supply, so that the auxiliary source barrel and the metal substrate produce glow discharge and arcing, bombarding and cleaning the high entropy alloy source target and the metal substrate, and the bombardment and cleaning are completed after the arcing phenomenon disappears; 1-3-2) Introduce argon, ammonia and methane with a purity of ≥99.99% into the equipment, wherein the flow rate of argon is 5-40mL / min, and the flow rates of ammonia and methane are 1-5mL / min. The vacuum degree is adjusted to a working pressure of 20-60Pa by adjusting the flow rates of the three gases; 1-3-3) gradually increase the voltage and current of the source pulse power supply of the equipment to make the temperature of the metal substrate 800-1400°C, and keep it warm for 2-5 hours. After the warming time is over, turn off the flow of argon, ammonia and methane to complete the infiltration deposition; 1-3-4) Carry out ion nitriding treatment: Ⅰ) introducing ammonia gas with a purity of ≥99.99% into the double glow plasma solid surface metallurgy equipment at a flow rate of 80-240 mL / min, controlling the glow thickness to be about 4-8 mm, the nitriding temperature to be 500-550° C., and adjusting the flow rate of ammonia gas introduced according to the glow thickness; II) The nitriding temperature is 480-560°C, the nitriding time is 5-10 hours, the source pulse power supply voltage and current are adjusted according to the nitriding temperature, and the pulse power supply voltage is controlled at -300V to -900V; Ⅲ) After the holding time is over, turn off the ammonia flow, turn off the power, keep pumping and allow the treated material to cool to room temperature with the furnace.
6. The method for preparing a biomedical gradient high entropy composite strengthening coating with an interstitial strengthening phase according to claim 3, characterized in that: In step 2-2), the ball milling process is as follows: under vacuum conditions, the ball milling speed is 30-90 r / min, the ball-to-material ratio is 15:1-18:1, the ball milling time is not less than 4 hours, and the alloy powder is obtained after sufficient mixing, and the particle size of the powder is 200-300 mesh.
7. The method for preparing a biomedical gradient high entropy composite strengthening coating with an interstitial strengthening phase according to claim 3, characterized in that: In step 2-3), the purity of the argon gas is ≥99.99%, and the gas flow rate is 20-30 L / min; the laser cladding surface treatment process is: the laser power is 3000-4000 W, the scanning speed is 3-6 mm / s, and the spot diameter D is 2-4 mm.
8. The method for preparing a biomedical gradient high entropy composite strengthening coating with an interstitial strengthening phase according to claim 3, characterized in that: In step 3-2), the ball milling process is as follows: under vacuum conditions, the ball milling speed is 240-280 r / min, the ball-to-material ratio is 10:1-12:1, the ball milling time is 1.5-2 hours, the inversion frequency is 30-45 Hz, and the alloy powder is obtained after sufficient mixing, and the particle size of the powder is 50-100 μm; In step 3-2), the pressure sintering process is as follows: under argon protection, the pressure in the pressure sintering furnace is 200-300 MPa, the sintering temperature range is 900-1000° C., and the holding time is 5-10 minutes.
9. The method for preparing a biomedical gradient high entropy composite strengthening coating with an interstitial strengthening phase according to claim 3, characterized in that: In step 3-3), the ion cleaning is to clean the dust and metal debris in the magnetron sputtering equipment, and then evacuate to 3×10-2Pa~3×10-3Pa, introduce argon gas, and adjust the gas flow rate to stabilize the gas pressure at 3~5Pa; finally, turn on the negative bias power supply, adjust the negative bias to the range of 500~800V, and perform ion bombardment glow cleaning for 15~20 minutes.
10. The method for preparing a biomedical gradient high entropy composite strengthening coating with an interstitial strengthening phase according to claim 3, characterized in that: In step 3-3), the process parameters of the magnetron sputtering are: anode substrate material temperature of 180-200°C, sputtering time of 40-50min, target substrate distance of 5-10cm, target power of 90-110W, and argon gas flow rate of 55-65sccm.
Citation Information
Cited By
Preparation method of high-temperature wear-resistant multilayer material on surface of precision part
CN119465059A
Spectral selective absorbing coating driven by anion-cation co-entropy engineering
CN121428475A
